CFD Study of the Effect of Surface Roughness on the Resistance of KVLCC2 tanker - عباس نوار; علي زينب (Latakia University Journal -Engineering Sciences Series, 2022)
This research aims to determine the effect of surface roughness on the resistance of KVLCC2 tanker at different values of roughness height and in several cases. The ship hull is divided into bow, middle parallel part (center) and stern. In the first cas This research aims to determine the effect of surface roughness on the resistance of KVLCC2 tanker at different values of roughness height and in several cases. The ship hull is divided into bow, middle parallel part (center) and stern. In the first case the whole surface of the ship hull was made rough, then only the surface of bow was made rough and the remained part of the hull was clean, in the third case only the middle part was made rough and finally, the stern was made rough. The RANS equations and k-ω SST model were used to solve the Navier Stocks Equations. To validate the CFD method, a benchmark test of plate with roughness was calculated. The numerical results show a good agreement with the experimental results. e the whole surface of the ship hull was made rough, then only the surface of bow was made rough and the remained part of the hull was clean, in the third case only the middle part was made rough and finally, the stern was made rough. The RANS equations and k-ω SST model were used to solve the Navier Stocks Equations. To validate the CFD method, a benchmark test of plate with roughness was calculated. The numerical results show a good agreement with the experimental results.